Evaluating Murābahah Contract Practices in BPRS Financing Agreement No. 8854/MBA/11/2010 and Associated Challenges in Islamic Banking - Wijaya, Adi; Fajriyati, Latifah Adi (STIS Ummul Ayman, Meureudu, Pidie Jaya, Aceh, Indonesia, 2024)
This research aims to analyze the application of the murābahah contract in BPRS financing agreement number 8854/MBA/11/2010 related to the payment period and problems that may arise in BPRS financing practices in Islamic banking. The research method uses a literature study that uses an empirical normative approach, which focuses on the application of normative law to certain legal situations that occur in society. the results showed that the application of the murābahah contract in the BPRS financing agreement Number 8854 / MBA / 11/2010 in the context of the payment period. In the application of the murābahah financing contract, the profit is not more than one-third or one-fifth and the repayment period is not more than three years because if it is more, it will cause ribā because the calculation uses a profit calculation instead of profit sharing as based on the calculation. second Problems that can occur in murābahah financing. In the practice of murābahah financing, there are various problems that can occur, including non-transparent margins, risks of ownership and storage, problems with the quality of goods, risk of bad financing, uncertainty of market prices, high involvement of third parties and the difficulty of renegotiating and if viewed from various aspects such as sharia aspects, legal aspects, and operational aspects, it is very likely that there will be a failure in the contract.